Pengembangan Aplikasi Perangkat Bergerak: Pencari Konselor Psikologi Terdekat berbasis Lokasi - Tifo Audi Alif Putra; Agi Putra Kharisma; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Mental health is now a problem that cannot be underestimated. Even mental health is now a problem faced by many countries in the world, including Indonesia. Depression is a major cause of mental health problems. Depression affects 4.4% of the world's population and 5% of the population in Indonesia. In addition to the high number of people with depression, another problem in Indonesia is the lack of available mental health professionals such as counselors and psychiatrists. Therefore, the use of mobile-based systems can be done to connect people who have problems with the nearest counselor to get first aid in the problem. The implementation of mobile application development in this study was developed on the iOS platform using the Swift programming language. The research method used is an iterative waterfall model consisting of needs analysis, system design, system implementation, and testing. Testing in this study consisted of blackbox testing and usability testing. In the blackbox testing the researchers designed a testcase scenario to assess the correct system behavior while to get the comfortability level of the application developed using the SUPR-Qm instrument. The test results on Blacbox Testing stated 100% valid of all designed testcases. For the usability test results obtained 69.25% for patient applications and 74.75% for counselor applications, then if converted to usability rating scale produces an ok category for patient applications and good for counselor applications.